Hollow Kingdom : a Novel - Buxton, Kira Jane (New York : Grand Central Publishing, 2019)
"One pet crow fights to save humanity from an apocalypse and the world that follows in this uniquely hilarious debut from a genre-bending literary author."--Publisher's description.
Keywords: Crows -- Fiction; Apocalyptic fiction; Fantasy fiction; Science fiction